Single Index Model Analysis for Optimum Portfolio in Pharmaceutical Companies Registered in Indonesia Stock Exchange - Agus Parhan Saepul Anwar; Ana Yuliana Jasuni; Andy Juniarso (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
Investment is an interesting thing to analyze during the Corona Virus Disease (COVID-19) pandemic because at this time the economy is experiencing a decline so specifically for investors, they must consider the level of risk in their shares. The purpose of this study is to determine the condition of Consumer Goods Industry stocks with a concentration of pharmaceutical companies that can form an optimal portfolio and to determine the proportion of each selected stock and the level of return and risk of the resulting portfolio. The method that used is Single Index Model approach. The results of the analysis show that using the Single Index Model, Consumer Goods Industry stocks with a concentration of pharmaceutical companies from December 2016 to November 2020 can form an optimal portfolio consisting of SIDO with a proportion of 26.10%, PYFA with a proportion of 23 , 02%, DVLA with a proportion of 50.89% and a portfolio expected return of 5.79% and a risk of 6.95%